La seguridad ciudadana y la influencia de la participación de la colectividad en las estrategias de prevención de la delincuencia en la parroquia el Sagrario del Cantón Loja - Faicán Sinchire, Andreina del Carmen (2024)
The objective of this research work was to analyze how the participation of the community influences crime prevention strategies with respect to citizen security, in the El Sagrario parish of the Cantón Loja, therefore we proceeded to determine the risk factors that they generate citizen insecurity; propose prevention strategies to reduce crime levels; and training will be generated to help increase citizen participation in security areas, to prevent the increase in crimes in the El Sagrario parish. To achieve these objectives, various methods were used such as deductive, analytical- synthetic and descriptive, and a mixed approach was applied combining theoretical research with the results obtained in the field. Likewise, the documentary review technique was used to obtain information and surveys to collect primary data. Finally, the analysis of the results obtained from the surveys carried out among the citizens of the Sagrario parish is presented, showing the responses obtained based on the events that have occurred in the study parish to the processes of citizen security and participation. of the community, where answers are given to the objectives set at the beginning of the investigation, where the conclusions and recommendations are also made known.